Plasma neurofilament heavy chain levels and disease progression in amyotrophic lateral sclerosis: insights from a longitudinal study. Issue 5 (9th July 2014) - Lu, Ching-Hua; Petzold, Axel; Topping, Jo; Allen, Kezia; Macdonald-Wallis, Corrie; Clarke, Jan; Pearce, Neil; Kuhle, Jens; Giovannoni, Gavin; Fratta, Pietro; Sidle, Katie; Fish, Mark; et al.
Abstract : Objective: To investigate the role of longitudinal plasma neurofilament heavy chain protein (NfH) levels as an indicator of clinical progression and survival in amyotrophic lateral sclerosis (ALS). Methods: A cross-sectional study involving 136 clinically heterogeneous patients with ALS and 104 healthy and neurological controls was extended to include a prospective analysis of 74 of these ALS cases, with samplings at approximately 3-month intervals in a follow-up period of up to 3 years. We analysed the correlation between longitudinal NfH-phosphoform levels and disease progression. Temporal patterns of NfH changes were evaluated using multilevel linear regression. Results: Baseline plasma NfH levels were higher than controls only in patients with ALS with short disease duration to baseline sampling. Compared with controls, fast-progressing patients with ALS, particularly those with a short diagnostic latency and disease duration, had higher plasma NfH levels at an early stage and lower levels closer to end-stage disease. Lower NfH levels between visits were associated with rapid functional deterioration. We also detected antibodies against NfH, NfH aggregates and NfH cleavage products. Conclusions: Disease progression in ALS involves defined trajectories of plasma NfH levels, reflecting speed of neurological decline and survival. Intervisit plasma NfH changes are also indicative of disease progression. This study confirms that longitudinal measurements of NfH plasma levels are more informative than cross-sectional studies, where the time of sampling may represent a bias in the interpretation of the results. Autoantibodies against NfH aggregates and NfH cleavage products may explain the variable expression of plasma NfH with disease progression. Trail registration number: NIHRID6160.